O enfermeiro e a avaliação do desenvolvimento neuromotor do lactente - Maia, Polyana Candeia (2013)
The evaluation of infant development is necessary to monitor and follow-up changes in children’s lives, seeking to identify their own characteristics and relate them to the respective human development stages. This study aims at evaluating motor development in children aged 2m15d to 12m15d. It is a descriptive-exploratory transversal study with an analytic approached carried out in Family Health Centers in the municipalities of Fortaleza and Sobral, Ceará, Brazil. The sample is composed of 330 children and their respective parents/caregivers, 165 from each referred municipality. Data collection took place from March to June 2012 using the Harris Infant Neuromotor Test (HINT) Brazilian version and the Ministry of Health Development Control Protocol, a form that includes socio-demographic data on parents/caregivers. Data was collected after approval granted by the Ceará Federal University Research Ethics Committee. Data was organized in Excel charts and analyzed through the SPSS version 18, and a Confidence Interval of 95% (p<0.05) was applied to all tests. Results showed that 52 Fortaleza children were aged 2m15d to 3m15d whereas in Sobral, 47 were between 11m16d and 12m15d. According to data, there was a significant statistical correlation between the baby delivery method and the two municipalities (p=0.020) and the marital status of Fortaleza mothers with the HINT final scores (p=0.035). There was also a remarkable difference in the Ministry of Health Development Protocol between term and preterm babies in Fortaleza (p=0.000) and Sobral (p=0.000) and the family income in Sobral (p=0.022). No statistically relevant differences were noticed between the two municipalities with regards to socio-demographic variables such as income, home floor type, basic sanitation and garbage collection. As for the HINT questionnaire directed to those responsible for looking after the children, in Fortaleza, 117 parents affirmed that they felt their baby was “strong and firm”, 88 of them stated that the child’s mobility was “excellent” and 85 reported that their children were “above expected standards” when compared to others of the same age. In Sobral, 132 parents affirmed to feel their child to be “strong and firm”, 92 said their mobility was “excellent” and 87 said that the child was in “normal development for his/her age”. The result of the neuromotor evaluation performance through the HINT program showed that most children, 98 (59.3%) in Fortaleza got a normal score and when evaluated through the Ministry of Health Control Protocol (Child Health Booklet) 127 (77%) in Fortaleza and 144 (87.3%) in Sobral were classified with adequate development. However, both instruments did not present a significant correlation between each other (K = -0.010). Despite this fact, both instruments proved to be useful for the target public, presenting advantages and disadvantages, which require further research with different samples and guidelines.